Inorganic reaction mechanisms. A personal journey. Issue 15 (12th March 2020) - Hubbard, Colin D.; Chatterjee, Debabrata; Oszajca, Maria; Polaczek, Justyna; Impert, Olga; Chrzanowska, Marta; Katafias, Anna; Puchta, Ralph; van Eldik, Rudi
Abstract : This review describes a personal journey over the past two decades highlighting experimental and computational mechanistic studies in inorganic chemistry performed with numerous PhD students, post-docs, visiting scientists and colleagues from abroad. Abstract : This review covers highlights of the work performed in the van Eldik group on inorganic reaction mechanisms over the past two decades in the form of a personal journey. Topics that are covered include, from NO to HNO chemistry, peroxide activation in model porphyrin and enzymatic systems, the wonder-world of Ru III (edta) chemistry, redox chemistry of Ru(iii ) complexes, Ru(ii ) polypyridyl complexes and their application, relevant physicochemical properties and reaction mechanisms in ionic liquids, and mechanistic insight from computational chemistry. In each of these sections, typical examples of mechanistic studies are presented in reference to related work reported in the literature.